FAKTOR – FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN INDEX LQ45 - Stephen Wahyudi Jaya; Rosmita Rasyid (Jurnal Paradigma Akuntansi, 2023)
The study was conducted to obtain empirical evidence of the effect of profitability. liquidity. Solvency, firm size. and dividend policy on firm value in companies listed on the LQ45 Index for the 2016 – 2019 period. The research design used is descriptive research using purposive sampling method and obtained 17 companies. This study uses multiple regression analysis which helps with the Eviews 10 application to test the data. The results obtained by the variables of profitability, solvency and firm size are able to have an influence on the firm value variable. This study also did not find a significant effect for liquidity and dividend policy. The implication of this research is the need for the company's attention to produce the ideal ratio, especially for profitability, solvency, and company sizewhich will affect the value of the company and will provide a good signal for investors.